Determination of Tofacitinib in Mice Whole Blood on Dried Blood Spots Using LC–ESI–MS/MS: Application to Pharmacokinetic Study in Mice - Dixit, Abhishek; Mallurwar, Sadanand Rangnathrao; Sulochana, Suresh P; Zainuddin, Mohd; Mullangi, Ramesh (Drug Research, 2019)
A simple, sensitive and rapid assay method has been developed and validated as per regulatory guideline for the estimation of tofacitinib on mice dried blood spots (DBS) using liquid chromatography coupled to tandem mass spectrometry with electro spray ionization in the positive-ion mode. The method employs liquid extraction of tofacitinib from DBS disk of mice whole blood followed by chromatographic separation using 5 mM ammonium acetate (pH 6.5):acetonitrile (20:80, v/v) at a flow rate of 0.60 mL/min on an X-Terra Phenyl column with a total run time 2.5 min. The MS/MS ion transitions monitored were m/z 313→149 for tofacitinib and m/z 316→149 for the internal standard (13C3,15N-tofacitinib). The assay was linear in the range of 0.99–1980 ng/mL. The intra- and inter-day precision was in the range of 1.17–10.3 and 3.37–10.9%, respectively. Stability studies showed that tofacitinib was stable on DBS cards for one month. This novel method has been applied to analyze the DBS samples of tofacitinib obtained from a pharmacokinetic study in mice.
Keywords: Tofacitinib; dried blood spot; LC-MS/MS; method validation; mice; pharmacokinetics